Auditoria de gestión al talento humano de la unidad educativa “Cascales” del cantón Cascales de la provincia de Sucumbíos, correspondiente al periodo 2014 - Vergara Lema, Norma Marilú (2016)
This thesis called "AUDIT OF HUMAN TALENT MANAGEMENT OF EDUCATIONAL UNIT “CASCALES” THE CASCALES CANTON IN THE PROVINCE OF SUCUMBÍOS, COVERING THE PERIOD 2014", It was developed based on the overall objective which is directed to conduct a management audit of the Human Talent Education Unit Cascales so we can give the specific objectives as perform internal diagnostics compliance, to determine the extent of compliance legal force, applying indicators of efficiency, effectiveness and economy Complying with audit phases : starting as preliminary knowledge , where the recognition of institution was performed , then it proceeded with the Preliminary Planning and specifies in which internal control is evaluated for knowing the activities of the Unit staff educational Cascales; in the execution and competent enough information it was obtained by applying the respective internal control questionnaires aimed at measuring the level of risk and management indicators to measure the degree of compliance ; then it proceeded to the preparation of the audit report on which are the most significant findings and the conclusions and recommendations . It is concluded that the Human Talent has not made him management indicators to measure the degree of compliance of its planned activities, the same that allows you to perform a proper performance evaluation carried out in the Education Unit